The Role of Emotional Intelligence in Managerial Decision-Making - Rajendra, Bryan (Generasi Sains Indonesia, 2024)
In this theoretical paper, the author seeks to discuss how emotional intelligence (EI) can play a crucial role in determining management decisions in the organization setting. Based on the existing theoretical frameworks and an extensive literature overview, the research reveals that the EI core competencies, including self-awareness, self-regulation, social awareness, and relationship management allow managers to be much more effective in handling complex decision-making frameworks. EI increases management abilities to identify and employ emotions, reduce prejudices, encourage teamwork, and propose good decision output. Although EI may not be the panacea to every other managerial issue, implementation of this concept in any leadership development program has been found to enhance the company performance and the involvement of its staff. The conclusion of the research on the matter is emotional intelligence is a very important skill in modern managerial profession, having significant bearing on the effectiveness of leadership and performance in an organization. It is suggested that future studies should focus on exploring the factors, which condition the impact of emotional intelligence on decision-making processes within context.